A bioinspired antibacterial and photothermal membrane for stable and durable clean water remediation. Issue 1 (22nd November 2022) - Yang, Yiyan; Yang, Lei; Yang, Fengying; Bai, Wanjie; Zhang, Xueqian; Li, Haotian; Duan, Gaigai; Xu, Yuanting; Li, Yiwen
Abstract : The tobramycin-doped polydopamine nanoparticles were developed to construct solar evaporator, which exhibited synergistic antibacterial behaviors and high water evaporation rate, thus achieving stable reuse even under microbe-rich environment. Abstract : Solar-driven steam generation has been considered as a prevalent and sustainable approach to obtain clean fresh water. However, the presence of microorganisms in seawater may cause the biofouling and degradation of polymeric photothermal materials and clog the channels for water transportation, leading to a decrease in solar evaporation efficiency during long-term usage. Herein, we have reported a facile strategy to construct a robust cellulose membrane device coated by tobramycin-doped polydopamine nanoparticles (PDA/TOB@CA). The PDA/TOB@CA membrane not only exhibited synergistic antibacterial behaviors with long-term and sustained antibiotic release profiles, but also achieved a high water evaporation rate of 1.61 kg m −2 h −1 as well as an evaporation efficiency of >90%. More importantly, the high antibacterial activity endowed the PDA/TOB@CA membrane with superb durability for stable reuse over 20 cycles, even in microbe-rich environments. Therefore, we envision that this study could pave a new pathway towards the design and fabrication of robust antibacterial and photothermal materials for long-term and stable clean water production.